„Zazdrośnik ten bezustannie usiłuje szkodzić tym, którzy szukają Boga”. Wpływ bytów demonicznych na losy jednostek i społeczności w "Historiach" Grzegorza z Tours - Ludewicz, Michal Jan (Vox Patrum, 2020)
Gregory of Tours’ Histories is one of the most important sources for the period of transition between antiquity and middle ages. It focuses on Gallic society. The main characters are kings of the Merovingian dynasty, landlords and bishops. Other than talking about its secular protagonists, Gregory pays some attention to spiritual beings. He is convinced about God’s providence and Christ’s role in the redemption of mankind. The bishop of Tours also supplies some information about evil beings: the Devil and demons. Gregory uses many names to describe the demonic reality, such as the Devil, Satan, Prince of Darkness, demon or demons. Even though he does not go into much detail about them, he gives an impression that he is aware of some internal hierarchy governing demonical beings. Gregory says a lot about actions taken by the Devil in the people of Gaul. He describes demonic possessions, acts of violence conducted under the inspiration of evil spirit as well as disorder caused by him in the community of Poitiers. Although the Evil One is strong and makes a lot of noise, it is still subordinated to Lord. Gregory shares with us his firm belief that the story of the world lies in the hands of God.